Snat10 Knockout Mice Cortical Neuronal Cells (ImageXpress XLS Example Images) - Georgiev, Polina; Blamey, Ben; Spjuth, Ola (Uppsala University, 2020)
Image set collected in the Spjuth Lab (https://pharmb.io/), used as a test dataset for the HASTE software tools, and referenced in associated publications.
The images are of Snat10 knockout mice cortical neuronal cells, grown for 7 days and treated with either hydrogen peroxide or glutamate.
In total, there are 2699 TIFF images, organized by wavelength.
Images were taken with an ImageXpress XLS, at the Spjuth Lab.
All the archives decompress into this path:./181214-KOday7-40X-H2O2-Glu/2018-12-14/9/*.tif
Keywords: Image processing; Medical and Health Sciences; Medicin och hälsovetenskap